Endoscopic Treatment of Black Esophagus With Fully Covered Metallic Stent - Ihsan Al Bayati MD; Vismay Badhiwala MD; Sarah Al Obaidi MD; Claudia Didia MD; Marc J. Zuckerman MD; Sherif Elhanafi MD (SAGE Publishing, 2022)
Acute esophageal necrosis (AEN) is a condition characterized by black appearance and inflammation of the esophagus. Our patient developed AEN presenting in the setting of alcohol intoxication and extensive inferior vena cava thrombosis. Esophagogastroduodenoscopy showed blood and black discoloration of the middle and lower esophagus with oozing. To control bleeding, a self-expandable fully covered metallic esophageal stent was placed. Multiple studies and reviews agree that the initial management for AEN is supportive care, resuscitation, and proton pump inhibitors to protect the esophageal mucosa from injury from acid reflux. Our case highlights the benefits of esophageal stent placement to manage AEN with active bleeding.